The Reunion as a Catalyst for Divorce: A Case Study of the Padang Religious Court, Indonesia - Halim, Syaflin; Asmaret, Desi; Mursal, Mursal; Daharis, Ade; Hebondri (Hukum Keluarga Islam IAIN LANGSA, 2024)
The occurrence of reunions has been recognized as a contributing reason to the increasing divorce rates in Padang City, with evidence of infidelity frequently associated with these gatherings. This paper examines the research gap about the function of reunions in divorce proceedings within the Religious Court jurisdiction of Padang City. The main aim is to investigate the impact of Islamic legal principles on divorce cases prompted by considerations connected to reunion. The study use a descriptive qualitative methodology to collect empirical data from real-world examples for comprehensive examination. This research distinctly emphasizes the convergence of social activities, such reunions, with legal and theological contexts, providing innovative insights into their role in marital strife. The results suggest that reunions may serve as a catalyst for marital breakdown, especially when preexisting relational difficulties are present. Court proceedings frequently exhibit elevated emotional tension, with judges and legal practitioners crucially responsible for upholding civility. Mediation efforts are often impeded by mistrust arising from reunion situations. Nonetheless, the application of Islamic law principles, including the prevention of harm and the promotion of justice, provides fair resolutions for both parties while striving to uphold the sanctity of marriage when possible. This research enhances the debate by recognizing reunions as a distinct and consequential social catalyst in divorce cases and suggesting Islamic legal strategies to alleviate their effects. These findings offer a novel viewpoint for policymakers and legal professionals to tackle rising issues in family law.